Conception d’une séquence d’apprentissage en français juridique (FOS), cas des étudiants de droit privé et droit international à l’université HAMMA Lakhder El-Oued - Ben Mebarek, Boumaraf, Nacer - Eddine Salem (جامعة الوادي University of Eloued, 2019)
différentes situations de communication du domaine juridique. Enfin, nous sommes arrrivés à confirmer que le module « terminologie », que font les étudiants à l’université ne suffit pas tout seul pour développer des compétences en langue française The 3rd year undergraduate students, who are enrolled in the Faculty of Law at Hamma University LAKHDER El-Oued find many difficulties in the French language, both orally and in writing. they believe that French is essential in their professional career. From our part, we see that the establishment of a training in FOS would be of considerable profitability for these future professionals in order to overcome the obstacles of the language. To this end, we took the initiative to design a learning sequence in FOS, based on the needs analysis of these students. To do this, we opted for two scientific investigation tools, the questionnaire to recount and analyze the needs and the research interview with specialists in the field to learn more and recognize the various communication situations of the legal field. Finally, we are ready to confirm that the terminology module, which students do at university, is not enough on its own to develop French language skills.
Keywords: FOS, analyse des besoins, séquence d’apprentissage, didactique du FOS; FOS, needs analysis, learning sequence, FOS didactics